A collection of suggested electronic course templates for use in higher education - Jill W. Fresen; Robin K. Hill; Fawei Geng (Association for Learning Technology, 2014)
The collection of electronic course templates suggested in this article results from collaborative investigation between instructional support staff and academic staff users of the virtual learning environment (VLE) at two institutions, one in the United Kingdom and the other in the United States. The particular VLE in use at both institutions was Sakai, although the experience described here can be applied to the design process and workflow using any VLE that allows the selection and some configuration of standard tools.We applied the lattice model of Hill, Fresen and Geng (2012) to design and build a set of six course site templates, which are used as the basis on which site owners can easily build new sites in the VLE. As the ultimate goal of template provision is to underpin pedagogy, academics are free to use a template or build a site from scratch, based on their own teaching context, and they may adapt any template according to the pedagogical purpose and nature of the course. The underlying assumptions are that academic staff retain full control over the content, tools and permissions in their new site. The templates are not mutually exclusive - that is, aspects from any template may be incorporated, where applicable, into another one.We conclude that it is helpful for the VLE support team to take the lead in proposing a set of templates according to the predominant teaching and learning models in use at a particular institution, which may contribute to consistency across course sites and ultimately result in an improved student learning experience.